2015
DOI: 10.4103/1817-1745.165727
|View full text |Cite
|
Sign up to set email alerts
|

Fatal cerebellar hemorrhage as an initial presentation of medulloblastoma in a child

Abstract: Children with medulloblastomas most commonly present with signs and symptoms of elevated intracranial pressure due to obstructive hydrocephalus, especially headaches and vomiting. However, some pediatric patients present with sudden neurological deterioration due to intracerebellar hemorrhage associated with medulloblastoma, although very few reports exist that document this phenomenon. An 8-year-old girl was admitted to our emergency department who presented with sudden loss of consciousness, vomiting, and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
(11 reference statements)
0
4
0
1
Order By: Relevance
“…It always occurs in children and severely affects the physical and mental health of children (Ramaswamy et al, 2016). The increase of intracranial pressure triggered by blockage of the fourth ventricle is the main symptom of medulloblastoma, which usually appears for 1 to 5 months before diagnosis (Menekse et al, 2015). Additionally, truncal ataxia, diplopia, papillae edema, cranial nerve palsy, vertigo and nystagmus are also common symptoms of medulloblastoma (Polkinghorn and Tarbell, 2007;Brasme et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It always occurs in children and severely affects the physical and mental health of children (Ramaswamy et al, 2016). The increase of intracranial pressure triggered by blockage of the fourth ventricle is the main symptom of medulloblastoma, which usually appears for 1 to 5 months before diagnosis (Menekse et al, 2015). Additionally, truncal ataxia, diplopia, papillae edema, cranial nerve palsy, vertigo and nystagmus are also common symptoms of medulloblastoma (Polkinghorn and Tarbell, 2007;Brasme et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that 2 patients were newly diagnosed with CRC during hospitalization for ICH, suggesting that ICH might be the first manifestation of CRC. Cancers with ICH as the initial symptom include choriocarcinoma, leukocythemia, and medulloblastoma[ 15 - 17 ]. How to quickly identify insidious cancer in patients with ICH is still a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Medulloblastoma can present heterogeneous features on MRI with variable enhancement patterns, cystic areas, hemorrhage and calcification [ 21 ]. Although intratumoral bleeding can be found in brain tumors, only few cases of medulloblastoma with spontaneous hemorrhages have been reported in the literature [ 5 , 22 ]. Park et al showed that the incidence of spontaneous hemorrhage was 5.6 % in patients with primary or recurrent medulloblastoma [ 23 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…However, the biological effect of Wnt/β-catenin signaling activation and the link with a better prognosis has not been clarified yet. Few cases of medulloblastoma presenting with spontaneous hemorrhage are reported in the literature [ 5 ]. Although some studies speculate on the etiology of the anomalous increased vascularization in medulloblastoma [ 6 ], a clear pathogenetic role has not been identified.…”
Section: Introductionmentioning
confidence: 99%